2018
DOI: 10.1108/sajbs-05-2017-0064
|View full text |Cite
|
Sign up to set email alerts
|

An empirical assessment of current accounts sustainability for major South Asian economies

Abstract: Purpose The purpose of this paper is to assess the sustainability of current accounts for five major South Asian economies, namely, India, Pakistan, Bangladesh, Sri Lanka and Nepal, for the period 1985–2016. Design/methodology/approach The study employs the intertemporal solvency model of Hakkio and Rush (1991) and Husted (1992). Autoregressive Distributed Lag bounds test, Gregory and Hansen’s test and Carrion-i-Silvestre and Sanso’s test are used to assess the cointegration between current account inflows a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Perron (1989) notes that standard unit root tests are biased in favor of the nonrejection of the null hypothesis of unit root when the data exhibit trend stationarity with a break. To deal with the problem, breakpoint unit root tests (based on modified ADF) have been used (Shastri et al , 2018 for details of the test).…”
Section: Research Methodology and Datamentioning
confidence: 99%
“…Perron (1989) notes that standard unit root tests are biased in favor of the nonrejection of the null hypothesis of unit root when the data exhibit trend stationarity with a break. To deal with the problem, breakpoint unit root tests (based on modified ADF) have been used (Shastri et al , 2018 for details of the test).…”
Section: Research Methodology and Datamentioning
confidence: 99%
“…Originally employed by Phillips and Hansen ( 1990 ), FMOLS has the benefit of erasing long-run correlation problems between stochastic regressor’s innovation and cointegrating equations whilst the DOLS delivers estimates which are efficient and unbiased for a small sample size (Kirikkaleli et al 2021 ). Also, the DOLS corrects for regressor endogeneity by including leads and lags of the first difference of the regressors (Shastri et al 2018 ). In a Vector Error Correction Model (VECM), short-term causality is indicated by changes in other differenced explanatory variables.…”
Section: Data Model and Econometric Methodologymentioning
confidence: 99%
“…Cunado et al (2010) reported little or no evidence of current account sustainability in the European countries. Shastri et al (2018) found strong sustainability in case of India, Bangladesh and Nepal, whereas weak sustainability was found for Sri Lanka and Pakistan pointing out the need for policy interventions. Camarero et al (2013) analysed the external sustainability group of 23 OECD countries and results suggested strong sustainability for six countries.…”
Section: Literature Overviewmentioning
confidence: 96%